Global Trends Athlete Performance Anxiety Research: Scopus Based Bibliometric and Network Analysis - Akhmad, Noor; Yuliawan, Ely; Rahman, Abdul; Babiera , Rene M. (LITPAM, 2026)
Performance anxiety in athletes is a critical issue in sport psychology because it may affect mental readiness, emotional regulation, physiological responses, and performance quality during competition. Although research on anxiety in sport has continued to expand, comprehensive scientific mapping of publication trends, collaboration patterns, and thematic directions remains limited. This study aims to analyze the development of research on performance anxiety, sports anxiety, and competition anxiety in athletes using a Scopus-based bibliometric approach. Data were retrieved from publications covering 1976-2025, with an initial search identifying 382 documents; after screening by document type, publication status, journal source, and language, 307 articles were included for further analysis. Bibliometrix, Biblioshiny, VOSviewer, and OpenRefine were used to examine publication trends, country and institutional contributions, author productivity, collaboration networks, and thematic structures. The findings show an annual publication growth rate of 2.27%, with a more pronounced increase after 2010. The United States, the United Kingdom, and Australia emerged as the leading contributors, while academic collaboration remains relatively fragmented. The dominant themes include anxiety, stress, mental health, coping, self-efficacy, and athlete well-being. This study confirms that athlete performance anxiety has evolved into a multidisciplinary research field with important implications for strengthening sport psychology, supporting athlete mental health, and developing evidence-based psychological interventions.